Textbook of medicine - Souhami, Robert L. (Robert Leon); Moxham, J. (John) (Churchill Livingstone, 2002)
Comprehensive and complete, the 4th Edition of this classic textbook thoroughly covers a full range of topics in general clinical medicine. It emphasizes practical aspects while also examining the growth in our understanding of the mechanisms of disease. A system-based organization makes information easy to find. A website gives access to more illustrations and case studies and includes multiple-choice questions.